SHIDDIQ DALAM PANDANGAN QURAISH SHIHAB - Almunadi, Almunadi (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2016)
This study concluded that the meanings of words Shidq Quraish Shihab always understood by people with any sense is always true and honest. They are not tainted by falsehood, nor does it take a position contrary to honesty, which looked dipelupuk their eyes only right, because it always gets divine guidance.